1988
DOI: 10.1123/jsep.10.3.307
|View full text |Cite
|
Sign up to set email alerts
|

Affective Outcomes in Competitive Youth Sport: The Influence of Intrapersonal and Socialization Factors

Abstract: This study was designed to examine potential correlates of positive and negative affect experienced by young athletes during a competitive sport season. An index of both positive affect, season-long enjoyment, and negative affect, competitive trait anxiety (CTA) were included. The study was grounded within Harter's (1978, 1981a) theory of competence motivation. Male and female participants (N=207) in an agency-sponsored youth basketball league completed self-report measures of self-esteem, perceived basketball… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
76
1
15

Year Published

1995
1995
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 138 publications
(96 citation statements)
references
References 19 publications
4
76
1
15
Order By: Relevance
“…In this study, enjoyment, which means "perceiving fun and pleasure in sports activities", was found to have a significant influence on female students' verbal skills. Sport enjoyment was associated with satisfaction of motor performance and higher degrees of perceived physical challenge and competence (Boyd & Yin, 1996;Brustad, 1988). Therefore, teachers should take consideration on the physical activity level when teaching female students in PE for the development of their verbal skills.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, enjoyment, which means "perceiving fun and pleasure in sports activities", was found to have a significant influence on female students' verbal skills. Sport enjoyment was associated with satisfaction of motor performance and higher degrees of perceived physical challenge and competence (Boyd & Yin, 1996;Brustad, 1988). Therefore, teachers should take consideration on the physical activity level when teaching female students in PE for the development of their verbal skills.…”
Section: Discussionmentioning
confidence: 99%
“…It should be noted, however, that a few studies have not found a significant relationship between self-evaluations and enjoyment (e.g., Brustad, 1988;Fox, Goudas, Biddle, Duda, & Armstrong, 1994;Scanlan, Carpenter, Lobel, & Simons, 1993 (Gould & Krane, 1992;Speilberger, 1966). Trait anxiety, on the other hand, is a more dispositional personality characteristic that predisposes individuals to perceive a wide range of situations as threatening and increases the likelihood of responding with heightened levels of state anxiety (Gould, 1993;Gould & Krane, 1992).…”
Section: Self-evaluations and Affectmentioning
confidence: 99%
“…For instance, a negative relationship between children's and adolescents' trait anxiety and global self-esteem has been reported (e.g., Brustad, 1988;Kerr & Goss, 1997). Similarly, Brustad and Weiss (1987) and Passer (1983) found that high trait anxious children and adolescents were lower in global self-esteem, although perceived physical competence was not found to vary between high-and low-anxiety groups.…”
Section: Self-evaluations and Affectmentioning
confidence: 99%
See 2 more Smart Citations